1986
DOI: 10.1159/000467891
|View full text |Cite
|
Sign up to set email alerts
|

Immunopharmacology of Anaphylatoxin-Induced Bronchoconstrictor Responses

Abstract: The complement anaphylatoxin peptides, C3a and C5a, are potential mediators of immediate hypersensitivity reactions, eliciting many of the same actions on isolated tissue and cell preparations as specific antigen. Instilled intratracheally in experimental animals, the peptides induce acute bronchospasms and are sometimes lethal. In vitro, they cause dosedependent contraction of isolated lung tissue preparations, a response which correlates well with bronchospasms observed in vivo, and our current understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Synthetic peptides, based on the carboxyl-terminal sequence of C3a, can also mimic these properties (53), and the addition of inhibitors to carboxypeptidase N potentiates the respiratory distress stimulated by instillation of C3a and C5a (54,55). Previous studies have suggested that these properties may be mediated in part by expression of leukotrienes, histamine, or plateletactivating factor (55,56). Whether the pulmonary changes are the direct result of C3a or C5a or are controlled through mediators regulated by these anaphylatoxins remains to be fully determined.…”
mentioning
confidence: 99%
“…Synthetic peptides, based on the carboxyl-terminal sequence of C3a, can also mimic these properties (53), and the addition of inhibitors to carboxypeptidase N potentiates the respiratory distress stimulated by instillation of C3a and C5a (54,55). Previous studies have suggested that these properties may be mediated in part by expression of leukotrienes, histamine, or plateletactivating factor (55,56). Whether the pulmonary changes are the direct result of C3a or C5a or are controlled through mediators regulated by these anaphylatoxins remains to be fully determined.…”
mentioning
confidence: 99%
“…It promotes multifarious in vitro reactions that include bronchoconstriction (8,9), edema formation, as well as attraction and activation of mast cells (10,11) and eosinophils (12,13); but it has no effect on neutrophil chemotaxis. C3a binds to a single ligand-specific receptor, the C3aR, which has only recently been cloned from several species including man, mouse, rat, and guinea pig (14 -19).…”
mentioning
confidence: 99%
“…Consequently, these animals have also been used to analyze C3a-induced bronchoconstriction, which can be antagonized by cyclooxygenase inhibitors but not antihistamines (8) similar to the situation in humans. Although an inbred guinea pig strain, called C2BB/R Ϫ , has been described that is nonresponsive to C3a in platelet-based assays (22), the molecular nature of this defect remained obscure and few animal studies have been performed with this strain (23).…”
mentioning
confidence: 99%
“…It did not accumulate in plasma unless the carboxypeptidase inhibitor EACA was present. These are all characteristics of CSa of most species (Vogt, 1974;Stimler, 1986 could explain the gradual differences between YAP and ZAP, in which soluble yeast products were absent.…”
Section: Discussionmentioning
confidence: 90%
“…Local release of an autacoid with this spectrum of activities is beneficial, e.g. by reducing endotoxin-induced lung injury (Ikeda et al, 1983), but systemic effects of PGI2 appear to be detrimental (Bult et al, 1980;Rie et al, 1983;Bult & Herman, 1985;Slotman et al, 1985;1986).…”
Section: Discussionmentioning
confidence: 99%